Pengaruh Iradiasi Gamma dan Penyimpanan Dingin terhadap Kandungan Proksimat, pH, dan ALT Filet Ikan Jenaha - Widya Pangestika; Satriya Abrian; Deden Yusman Maulid; Kusuma Arumsari; Sugili Putra; Farakh Fadila Windiarti; Vipi Herawati (Jurnal Pengolahan Hasil Perikanan Indonesia, 2022)
Fish and fishery products are perishable foodstuffs. One technology to prolong the shelf life of fish is gamma irradiation. Irradiation is able to break the bonds of bacterial DNA chains, thereby inhibiting bacterial growth. The application of irradiation technology will certainly be much more effective when combined with other preservation technologies, such as storage at cold temperatures. In this study, skinless jenaha fish fillet (Lutjanus sp.) was irradiated at doses of 0 kGy, 3 kGy, 5 kGy, and 8 kGy. After being irradiated at a certain dose, fish fillets were stored for 6 days at a cold temperature of 5oC. Based on the results of the proximate analysis, it was found that irradiation technology did not cause significant changes to the moisture content, ash content, and fat content but slightly reduced the protein content of fish fillets. Furthermore, it was found that in terms of pH, fish fillets that were not irradiated and irradiated fish fillets were still categorized as fresh fillets until storage on the 6th day. Although the amount of bacterial contamination in fish fillets that were not irradiated was much greater than that of irradiated fish fillets, the number of bacterial contaminants in all treatments of fish fillets was still below the threshold set by SNI 7388: 2009. The pH value and the amount of bacterial contamination in all treatments Fish fillets tend to increase with the length of the storage process.